Nature-based green infrastructure: A review of African experience and potential - Mairi Dupar; Elvina Henriette; Eric Hubbard (Overseas Development Institute (ODI), 2023)
The African continent needs 68-108 billion in new financing each year to bridge its critical infrastructure gaps, according to President Adesina of the African Development Bank. Meanwhile, the International Monetary Fund (IMF) calculates that climate change adaptation alone will cost Africa up to 50 billion annually, equivalent to about 3% of regional GDP. Given Africa's needs, nature-based solutions for green infrastructure (NBS-GI) are accorded high political priority by African leaders, with three ecosystem restoration trends - land degradation neutrality, catchment restoration, and coastal ecosystem restoration - increasingly prevalent on the continent. NBS-GI can improve people's food and income security, enhance biodiversity, and contribute to climate change adaptation and mitigation efforts. This report explores the existing and potential role of NBS-GI in disaster risk management and climate change mitigation and adaptation, as well as wider development objectives. The research focuses on the application, financing and efficiency of NBS-GI in African contexts, as well as on the motivations for selecting NBS-GI investments in Africa.
Keywords: 330; Adaptation; Environment; South Africa; Kenya; Sudan; Bio-diversity; Africa; Climate change; Tanzania; Seychelles; Egypt; Madagascar; Disaster risk reduction; Sierra Leone